Juridical analysis of legal protection for creditors on the validity of the Power of Attorney to Encumber Mortgage (SKMHT) executed before a notary from the perspective of security law - Metta Tjia; Markus Gunawan; Irpan Husein Lubis (Goodwood Publishing, 2025)
Purpose: This study analyzes the legal protection of creditors regarding the validity of the Power of Attorney to Encumber Mortgage Rights (Surat Kuasa Membebankan Hak Tanggungan/SKMHT) made before a Notary. It specifically examines differences in SKMHT formats between Notaries and Land Deed Officials (PPAT) and their implications for creditor protection and integration with land registration systems. Methodology: A descriptive juridical-sociological approach was employed, combining normative legal analysis with empirical research. Data collection involved statutory and literature reviews as well as field research, including interviews with notaries, PPATs, and land office officials. Results: The study reveals that creditor protection in Indonesia remains fragmented under several legal instruments such as the Civil Code, Mortgage Law, Banking Law, and Notary Law. Land offices generally require SKMHTs to comply with formats issued by the Head of the National Land Agency for integration with the electronic mortgage system (HT-el), creating challenges for SKMHTs drafted by Notaries. Conclusion: The research concludes that harmonization between the Notary Law and agrarian laws is essential to ensure uniform recognition of SKMHTs across institutions, thereby strengthening legal certainty for creditors and improving the effectiveness of the electronic mortgage registration system. Limitation: The study is limited to SKMHT implementation in Indonesia and does not include a comparative assessment with other jurisdictions. Contribution: This research contributes by identifying regulatory gaps and offering harmonization measures to reinforce creditor protection, improve procedural uniformity, and support the effective operation of the electronic mortgage registration framework.